2018
DOI: 10.1111/tpj.13959
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of lipid metabolites and expressed genes reveals tissue‐specific heterogeneity of lipid metabolism in high‐ and low‐oil Brassica napus L. seeds

Abstract: Despite the importance of oilseeds to worldwide human nutrition, and more recently to the production of bio-based diesel fuels, the detailed mechanisms regulating seed oil biosynthesis remain only partly understood, especially from a tissue-specific perspective. Here, we investigated the spatial distributions of lipid metabolites and transcripts involved in oil biosynthesis from seeds of two low-erucic acid genotypes of Brassica napus with high and low seed-oil content. Integrated results from matrix-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 68 publications
(113 reference statements)
2
68
0
Order By: Relevance
“…In oilseeds, TAGs are primarily stored in the embryo, which consists of outer cotyledons (OC), inner cotyledons (IC), and an embryonic axis (EA) Woodfield et al, 2017;Lu et al, 2018). Previous studies of B. napus seeds with low erucic acid content have shown that total lipids and lipid molecular species are differentially distributed across its seed tissues Woodfield et al, 2017;Lu et al, 2018). Although the metabolism of erucic acid is understood, the spatial distribution of lipids containing erucic acid has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In oilseeds, TAGs are primarily stored in the embryo, which consists of outer cotyledons (OC), inner cotyledons (IC), and an embryonic axis (EA) Woodfield et al, 2017;Lu et al, 2018). Previous studies of B. napus seeds with low erucic acid content have shown that total lipids and lipid molecular species are differentially distributed across its seed tissues Woodfield et al, 2017;Lu et al, 2018). Although the metabolism of erucic acid is understood, the spatial distribution of lipids containing erucic acid has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The content of PS with >36 acyl carbons was the highest species in each tissue (Devaiah et al, ), and our results showed PS‐42:1 was the highest PS species in 4 rapeseed tissues (Figure b). The content of TAG‐54:3, TAG‐54:4, TAG‐54:5, PC‐36:2, and PC‐36:3 was the most abundance species in TAG and PC in mature rapeseed detected by MALDI‐MS and ESI‐MS/MS (Lu et al, ). These data were consistent with previous reported results that TAG‐54:3, TAG‐54:4, and TAG‐54:5 were the highest content species in TAG in 56 DAF seed.…”
Section: Discussionmentioning
confidence: 99%
“…(g) The content of TAG species in different tissues. Heat map was drawn by software ImageGP rapeseed detected by MALDI-MS and ESI-MS/MS (Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The expression profile of a gene in a specific plant tissue provides clues related to its function under a particular conditions or a stage of growth and development. Using tissue-specific transcriptome analysis, Lu et al (2018) identified key genes with different expressions in individual organs involved in de novo fatty acid biosynthesis that affect lipid metabolism and oil content in Brassica napa seeds. In the case of CBLs, it has been shown through promoter-β-glucuronidase activity that CBL1 and CBL9 are expressed in leaves, roots, flowers, and vascular tissues in Arabidopsis (Pandey et al 2004, Cheong et al 2007 whereas CBL4 is mainly expressed in root tissue (Quan et al 2007) and CBL10 in the shoot tissue (Cheong et al 2010).…”
Section: Discussionmentioning
confidence: 99%